PENENTUAN ZONA PRIORITAS RUANG TERBUKA HIJAU BERDASARKAN URBAN HEAT ISLAND DI KOTA YOGYAKARTA, PROPINSI DAERAH ISTIMEWA YOGYAKARTA - , RATIH PURNAMASARI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The development of built area reduces green open space and increases the temperature at urban areas. The significant temperature difference between urban areas and its surroundings is known as urban heat island phenomenon. The purposes of this research are